Традиції та вірування гірників середньовічної Європи як організаційний фактор становлення й розвитку гірничих спільнот - Гайко, Геннадій Іванович; Білецький, Володимир Стефанович (Український культурологічний центр, 2014)
У статті аналізуються малодосліджені питання організації гірничих спільнот середньовічної Європи. Розкрито роль традицій та вірувань гірників у становленні й розвитку гірничої діяльності. Показана роль ченців-цистерціанців у започаткуванні гірничого промислу в Середній Європі. Досліджено вплив християнських традицій на організацію життя гірників. Окреслено "пантеон" святих заступників гірників, зокрема св. Варвари. Поруч із християнськими показані поганські вірування й забобони гірничого світогляду. Розглянуто питання відродження кращих традицій у сучасному студентському й професійному середовищі гірників.

Little-studied issues of miners' society organization is analyzed in the article. Role of miners' traditions and beliefs is shown in foundation and development mining. Influence of Cistercian Order for beginning of mining was under consideration. Monastic organization and religious motivation of "White Friars" for mining were scope. Christian and professional traditions' influence on life organization of mining artelsand on formation special feature of miners' societies was reveal. Tutelar saints of miners were describe, particular - St. Barbara. Traditions and beliefs were considered from the side of mining society's separateness, protection of miner's knowledge and experience from widespread occurrence, it gave them special privileges. Question of tradition revival for modern professional and students' environment was studied.
Miner's traditions and beliefs in medieval Europe like organizational factor of mining society's formation and development
Keywords: гірничі традиції; вірування; християнські заступники гірників; чернечі ордени; цистерціанці; організаційний фактор; мотиваційні моделі; гірничі спільноти; miners' traditions; beliefs; tutelar saints of miners; monastic order; Cistercians; organizational factor; motivation model; miners' societies; mining law